Posterior reversible encephalopathy syndrome and anti-angiogenic agents: a case report - Silva, F (2012)
Posterior reversible encephalopathy syndrome is an increasingly recognised clinico-radiological entity, associated with several medical conditions (such as systemic arterial hypertension) and characterised by seizures, altered mental status, headaches, and visual symptoms. Magnetic resonance imaging is a key component in this diagnosis, with hyperintense foci in T2-weighted images, corresponding to vasogenic oedema. The pathophysiology is not fully understood but probably involves loss of auto-regulation of cerebral vasculature or endothelial dysfunction or both. A 56-year-old male, suffering from a gastro-intestinal stromal tumour with hepatic metastasis resistant to imatinib, on therapy with sunitinib, came to the Emergency Department because of headaches, hallucinations, and loss of vision. There was no previous history of high blood pressure. A hypertensive crisis was diagnosed; ophthalmological examination on admission showed no light perception bilaterally. Brain imaging displayed bilateral parieto-occipital and frontal vasogenic oedema, consistent with the clinical diagnosis of posterior reversible encephalopathy syndrome. After treatment of hypertension and suspension of sunitinib, the patient recovered from his symptoms. Control imaging showed no oedema. Angiogenesis inhibitors, such as sunitinib and bevacizumab, can cause hypertension, one of the many medical conditions associated with the posterior reversible encephalopathy syndrome. This syndrome should be considered in cases of acute visual loss, particularly in view of its reversible nature when diagnosed and treated promptly.